Creating Tunable Micro-Optical Components via Photopolymerization 3D Printing Combined with Polymer-Dispersed Liquid Crystals - Sheng-Yuan Zhang; Hsi-Fu Shih; Chuen-Lin Tien; Han-Yen Tu (Micromachines)
Based on additive manufacturing via photopolymerization, this study combines polymer-dispersed liquid crystal (PDLC) technology with 3D printing technology to produce tunable micro-optical components with switchable diffraction or focusing characteristics. The diffraction grating and Fresnel zone plate are the research targets. Their structures are designed and simulated to achieve expected optical functions. A liquid crystal display (LCD) 3D printer is used to produce structures on transparent conductive substrates. The printed structures are filled with PDLCs and covered with transparent conductive substrates to achieve tunable functions. The proposed configurations are implemented and verified. The experimental results show that the diffraction efficiency of the 0th order increases from 15% to 50% for the diffraction grating and the focusing spot intensity decreases from 74% to 12% after the application of an electric field. These results demonstrate the feasibility of the proposed tunable optical component configurations.